Pattern of Residual Stress Formation at Gas-Thermal Coating Deposition - A. F. Ilyuschenko; S. S. Makarevich; Zh. A. Mrochek; L. M. Kozhuro; M. F. Pashkevich (Наука и техника)
The paper shows that gas-thermal coatings on the product surface may be considered on a first approximation as bimetallic material. Such approach permits to make calculations and determine residual stresses on the basis of multi-layer plate theory, mechanics of continuous medium and thermoelasticity.